Innovative approaches to accounting education: incorporating business intelligence tools - Mohammed M. Yassin; Ahmad A. Toumeh (Cogent Business & Management, 2024)
This study explores innovative approaches to accounting education by incorporating business intelligence (BI) tools. With the rapid advancement of technology and increasing complexity of business operations, traditional accounting education methods are being challenged to keep pace with industry demands. A total of 395 questionnaires were distributed to professional accountants and academic staff members. Data analysis entailed both descriptive and inferential statistics. The analysis revealed distinct insights into the perceptions of incorporating BI tools into accounting curricula. Integration of BI tools in accounting education assures transformative effects, as highlighted by positive responses regarding curriculum adaptation, skills, and competencies as well as career transformation. Furthermore, discrepancies between academics and professionals in research focus confirm the need for further investigation into BI-based accounting. This study shows the significance of BI tools in accounting education for academics, highlighting the need to update curricula to incorporate these advancements. This emphasizes the pivotal role that BI technology plays in advancing accounting practices. Consequently, teaching methods and course materials should evolve to enhance students' skills and increase their employability, thereby contributing to a more competitive workforce.
Keywords: 650; ccounting education innovation; business intelligence tools; curriculum adaptation; research focus; skills and competencies; interdisciplinary collaboration; career transformation